2015
DOI: 10.17925/enr.2015.10.02.171
|View full text |Cite
|
Sign up to set email alerts
|

Treating Drug-resistant Epilepsy – Why are we Waiting?

Abstract: Drug-resistant epilepsy (DRE) has been defined by the ad hoc Task Force of the International League Against Epilepsy (ILAE) Commission on Therapeutic Strategies as the failure of two appropriately chosen and tolerated anti-epileptic drugs (AEDs) (whether as monotherapy or in combination) to control seizures when used for an adequate period of time. The difference between the number of patients with DRE and the number of these patients who do not get access to adequate treatment is defined as the 'treatment gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It has been reported that the prevalence of epilepsy in the general population is approximately 1%, approximately 30-40% of patients with epilepsy are drug resistant, and epilepsy surgery is safe and effective for these patients. [8][9][10] However, only 36% of patients with drug-resistant epilepsy undergo a comprehensive epilepsy evaluation 11) and less than 1% of patients with epilepsy are referred to full-service epilepsy centers to be assessed for surgical eligibility. [11][12][13] Furthermore, it has been reported that only 1-2% of patients with drug-resistant epilepsy ultimately undergo surgery, and some of them are referred to low-volume, non-academic hospitals where treatment outcomes are worse and complication rates are higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the prevalence of epilepsy in the general population is approximately 1%, approximately 30-40% of patients with epilepsy are drug resistant, and epilepsy surgery is safe and effective for these patients. [8][9][10] However, only 36% of patients with drug-resistant epilepsy undergo a comprehensive epilepsy evaluation 11) and less than 1% of patients with epilepsy are referred to full-service epilepsy centers to be assessed for surgical eligibility. [11][12][13] Furthermore, it has been reported that only 1-2% of patients with drug-resistant epilepsy ultimately undergo surgery, and some of them are referred to low-volume, non-academic hospitals where treatment outcomes are worse and complication rates are higher.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] However, only 36% of patients with drug-resistant epilepsy undergo a comprehensive epilepsy evaluation 11) and less than 1% of patients with epilepsy are referred to full-service epilepsy centers to be assessed for surgical eligibility. [11][12][13] Furthermore, it has been reported that only 1-2% of patients with drug-resistant epilepsy ultimately undergo surgery, and some of them are referred to low-volume, non-academic hospitals where treatment outcomes are worse and complication rates are higher. 14) Therefore, one study recommended that in order to provide many more patients with refractory epilepsy with safe and effective surgical therapy, the number of referrals to full-service epilepsy centers offering specialized diagnosis and other alternative treatments, as well as psychosocial support, should be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Sudden unexpected death in epilepsy (SUDEP) is the main cause of death in patients with DRE and accounts for up to 50% documented causes of death in this group of patients (Opeskin and Berkovic 2003;Tomson et al, 2008;Surges et al, 2009;Shorvon and Tomson, 2011). Therefore, the main goal of DRE therapy is to extend the seizure control period, minimize side effects and improve quality of life (Boon et al, 2015). Currently, a number of scientific studies include the use of natural substances with antiepileptic properties as adjuncts to standard antiepileptic drugs in the DRE treatment and flavonoids and may be a potential group of natural drugs that increase the effects of commonly used anticonvulsants.…”
Section: Introductionmentioning
confidence: 99%